HIV Risk Perceptions, the Transition to Marriage, and Divorce in Southern Malawi. Issue 3 (September 2014) - Grant, Monica J.; Soler‐Hampejsek, Erica
<x xml:space="preserve">Abstract</x> Little is known about whether the timing of marriage is used as a strategy to avoid HIV infection among young people in sub‐Saharan Africa. Analyzing five rounds of longitudinal data from the Malawi Schooling and Adolescent Survey, we do not find support for the hypothesis that young women's perceived chances of future HIV infection are associated with the transition to marriage, but we do find evidence that young married women who see themselves as at risk of future infection have a greater likelihood of divorcing than do women who perceive no chance of future infection. We also use individual‐level fixed‐effects regressions to examine how the transition to marriage affects respondents' expectations of future HIV infection. Respondents are consistently more likely to perceive any chance of future HIV infection in the years following marriage than in the years preceding it. Our findings suggest that young women revise their risk perceptions based on their marital experiences and that divorce may serve as a protective strategy for young married women concerned about their chance of future HIV infection.